DETERMINANTS OF STOCK PRICES VOLATILITY GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE - Valeria Vivi Silvia; Santoso, Hadi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: Focusing on stock price volatility, this research investigates the roles of trading volume, leverage, and dividend policy, with corporate governance examined as a potential moderator. The main aim is to establish whether corporate governance can reinforce the relationships between the independent variables and stock price volatility. Interest in this topic was triggered by differences in findings in previous studies. The object of this study covers all companies listed on the Indonesia Stock Exchange (IDX) except for the non-cyclical sector, with a research period from 2020 to 2024.Methods: A quantitative research design was applied, drawing secondary data from corporate financial and annual reports, Yahoo Finance, as well as other pertinent sources. The sample was selected based on purposive sampling criteria, which resulted in 72 companies over 5 years of observation, with a total of 360 observations. The data was analyzed using Eviews 13 with Moderated Regression Analysis (MRA).Results: Trading volume had no impact on stock price volatility, while leverage and dividend policy had a significant effect and positive. Meanwhile, the moderation test results showed that corporate governance strengthened the effect of trading volume on stock price volatility. However, corporate governance weakened the effect of leverage and dividend policy on stock price volatility. Keywords: Corporate Governance, Dividend Policy, Leverage, Stock Price Volatility, Trading Volume.